Adrenarche, social cognition, and the development and evolution of autism spectrum traits - Szakal, Cory; Crespi, Bernard (Frontiers in Psychiatry, 2025)
Autism Spectrum Disorder (ASD) is a heterogeneous neurodevelopmental condition characterized by underdeveloped social cognition, along with restricted interests and repetitive behaviors. ASD manifests through a range of genetic, environmental, and psychosocial factors, which influence brain development and lead to maladaptive social and behavioral processes. While early diagnosis is common, ASD traits can develop and express themselves through various stages of childhood, driven by dynamic changes in cognitive and social abilities in relation to stressors and challenges. A recent study reports genomic and psychological evidence for two different age-related trajectories of autism development, one early, and one later and near the time of adrenarche and middle childhood, around ages 7 - 10. Given that middle childhood represents a key period for the development of social cognition including complex theory of mind and peer relationships, that adrenarche mediates the origin and social adaptations of middle childhood, and that social challenges increase with its onset, we hypothesize that autism onset, expression and diagnoses during this period may involve alterations to adrenarche, and to its endocrinological and neurological bases. Adrenarche involves onset and increase in secretion of the androgens dehydroepiandrosterone (DHEA) and its sulfate (DHEAS). A series of systematic reviews was conducted to evaluate the hypothesis that DHEA or DHEAS levels are associated with ASD, autism spectrum traits, or aspects of brain development relevant to autism. The reviews showed that: (1) higher DHEA demonstrated evidence of positive associations with aspects of internalizing and externalizing, including social anxiety, with especially notable effects in girls, and (2) higher DHEA showed evidence of association with ASD diagnoses overall, as also indicated by a recent meta-analysis. These findings provide initial support for the hypothesis that alterations to the social adaptations associated with adrenarche, and DHEA levels in middle childhood may underlie a subtype of autism with diagnosis during this developmental period.